Strangers in Paradigms!? Alternatives to Paradigm-Bound Methodology and Methodological Confessionalism - Udo Kelle; Florian Reith (Forum: Qualitative Social Research, 2023)
In our paper we discuss and criticize an idea which is often taken for granted in methodological discourses about mixed methods: namely that social researchers in general and mixed methods researchers in particular have to adopt a specific epistemological paradigm (a set of beliefs which have to be accepted a priori) before they can meaningfully perform research. By examining different versions of this model of paradigm-bound methodology which Yvonna LINCOLN and Egon GUBA had developed between the 1980s and 2010s, we will discuss implications of the notion paradigm and show that several of the paradigms proposed as the basis of research (e.g., positivism or constructivism) are ill-defined, lack coherence and are only superficially related to actual developments in the history of philosophical thought or contemporary epistemological debates. As an alternative to paradigm-bound methodology we will propose that researchers apply methods in an epistemologically informed way by employing epistemological concepts not as immutable givens but as heuristic devices which are used to identify and solve methodological problems. We will exemplify our approach by means of data from our own mixed methods study in which we simultaneously drew on realist and constructivist concepts to foster the understanding of contradictory statistical results.